Biological aspects of Aphis gossypii Glöver, 1877 (Hemiptera: Aphididae) on colored lint cotton cultivars - Correa, Lilian Roberta Batista [UNESP]; Cividanes, Francisco Jorge [UNESP]; Sala, Saulo Rene Damião [UNESP] (Instituto Biológico, 2013)
This paper outlines the results of a study into the biological aspects of Aphis gossypii Glöver on colored cotton cultivars through the construction of life tables. In addition, we evaluate the influence of density of gossypol glands and trichomes of leaves on the biology of the aphid. Tests were conducted in a climate chamber at 25 ± 2°C, with relative humidity (RH) at 70 ± 10%, and a photophase of 12 hours, using the cultivars BRS Rubi, BRS Safira, and BRS Verde. Newly hatched nymphs were individually isolated in petri dishes containing leaf discs of cotton cultivars on a layer of water-agar (1%) of approximately 5 mm thick. An evaluation of the trichomes and gossypol gland densities of the cotton leaf plants was performed under a stereomicroscope, delimited to an area of 1 cm², and a count and identification of those on the surface was made. The feed substrates that were evaluated influenced the nymphal stage of A. gossypii. BRS Verde provided the shortest duration and BRS Safira was the longest during this phase. The cultivar BRS Verde, with the lowest density of trichomes, provided a large number of nymphs and led to a higher net reproductive rate (R0). Given these results, conclusions can be drawn that the colored cotton cultivars influence the duration of nymphal and adult stages of A. gossypii. The cultivar with a high density of trichomes on leaves (BRS Safira) adversely affects the fertility parameters of A. gossypii.

Este trabalho teve por objetivos estudar aspectos biológicos de Aphis gossypii em cultivares de algodoeiro de fibra colorida, construir tabelas de vida e avaliar a influência da densidade de tricomas e glândulas de gossipol das folhas das plantas na biologia do pulgão. Os ensaios foram conduzidos em câmara climatizada regulada a 25 ± 2°C, UR de 70 ± 10% e fotofase de 12 horas, utilizando-se as seguintes cultivares: BRS Rubi, BRS Safira e BRS Verde. Ninfas recém-nascidas foram isoladas individualmente em placas de Petri contendo discos foliares de algodoeiro das cultivares sobre uma lâmina de ágar-água (1%) de aproximadamente 5 mm. A avaliação da densidade de tricomas e de glândulas de gossipol das folhas das plantas foi realizada sob microscópio estereoscópico, delimitando-se uma área de 1 cm² e, em seguida, realizando-se a contagem e identificação dos mesmos nessa superfície. Os substratos alimentares avaliados influenciaram a fase ninfal de A. gossypii, sendo que a BRS Verde proporcionou menor tempo de duração e a BRS Safira, o maior período desta fase. A cultivar BRS Verde com a menor densidade de tricomas proporcionou elevada produção de ninfas e a maior taxa líquida de reprodução (R0). Diante dos resultados, conclui-se que as cultivares de algodoeiro colorido influenciam o tempo de duração da fase ninfal e adulta do pulgão A. gossypii. A cultivar com elevada densidade de tricomas nas folhas (BRS Safira) afeta adversamente os padrões de fecundidade de A. gossypii.
Aspectos biológicos de Aphis gossypii Glöver, 1877 (Hemiptera: Aphididae) em cultivares de algodoeiro com fibra colorida
Keywords: cotton aphid; colored lint; Biology; trichomes; gossypol; Pulgão do algodoeiro; Fibra colorida; Biologia; tricomas; gossipol